PERAN BADAN KOMUNIKASI PEMUDA REMAJA MASJID INDONESIA (BKPRMI) DALAM MENGURANGI BUTA AKSARA ALQURAN MAJELIS TAKLIM DI DESA BORIMATANGKASA KECAMATAN BAJENG BARAT KABUPATEN GOWA (Jurnal Washiyah: Jurnal Kajian Dakwah dah Komunikasi, 2022)
This research raises the main issue of the Role of the Indonesian Mosque Youth Communication Agency (BKPRMI) in Reducing Quranic Illiteracy of the Taklim Assembly in Borimatangkasa Village, West Bajeng District, Gowa Regency. This research used a type of descriptive qualitative research whose research location was carried out in the village in Borimatangkasa Village, West Bajeng District, Gowa Regency. The primary data source in the study was Ustadz Irwan (Chairman of the BKPRMI DPK in West Bajeng District) as a key informant and additional informant there were 6 people, namely: Fatahuddin Dg Nyengka (Deputy Chairman of the BKPRMI DPK), Amiruddin (Chairman of LPPTKA), and taklim assembly members, namely Hawiyah Dg Ngintang, Kamariah Dg Bulang, Syukriani Dg Bulang, Kasmawati Dg Caya. The results of this study show that the efforts of the Indonesian Mosque Youth Communication Agency (BKPRMI) in Reducing Quranic Illiteracy of the Taklim Assembly in Borimatangkasa Village, West Bajeng District, Gowa Regency, there are 3. First is the Dirosa approach. Both approaches iqro. All three approaches qiro'ati. Supporting and inhibiting factors are: there are 3 supporting factors, namely, first, cooperation between BKPRMI administrators and mosque administrators. Second, there are facilities and infrastructure available. The three high-key taklim Nurul iman assemblies. There are 3 inhibiting factors, namely, the frequent lateness of going to recitation, secondly the busyness of the taklim assembly, and the third is the lack of awareness.